Analysis on Non Muslim Heir Position Towards the Inheritance of Muslim Testator in Indonesia - Tonic Tangkau; Daniel Julian Tangkau; Prawitra Thalib; Xavier Nugraha; Windy Agustin (Yuridika, 2019)
Article 171 section c the Compilation of Islamic Law which was ratified through the Presidential Instruction of the Republic of Indonesia Number 1 of 1991 stressed that one of the conditions for heirs in Islamic inheritance law is Mulsim. In its development, the requirement of the Islamic religious obligation is deemed not to provide justice, this can be seen from the many complaints filed by the community to the court. Based on this background, the formulation of the problem in this study is Firstly position of Non-Muslim Inheritance of Islamic Inheritance Inheritance according to positive law in Indonesia Secondly, to find out the position of Non-Muslim Inheritance Against Islamic Inheritance Inheritance from various court decisions in Indonesia. This research is a juridical research, with a statutory, conceptual, and case approach. The results of this study indicate, that First, according to positive law in Indonesia, Non-Muslim Heirs are not entitled to Islamic Inheritance. Secondly, in its development, to fulfill the sense of justice in the community, the judge in Indonesia, decided that the Non-Muslim heirs, although not entitled to become heirs, were still entitled to the inheritance of the Islamic heirs through the obligatory wills. This can be seen from the various court decisions that exist, such as Supreme Court Decision Number 368 K/AG/1995, Supreme Court Decision Number 51 K/AG/1999, Supreme Court Decision Number 16 K/AG/2010, and Supreme Court Decision No. 331 K/Ag/2018